New Developments for the Qualification of Technical Surfaces in Forming Processes - Geiger, Manfred; Engel, Ulf; Pfestorf, Markus (CIRP Annals - Manufacturing Technology, 1997)
In modern sheet metal forming, blank topographies are characterized by various quite different and rather sophisticated structures. This is due to the various deterministic or semi-deterministic methods of surface texturing produced by skinpass rolling. The conventional surface parameters determined from profile data are not capable of characterizing such surfaces, in particular with respect to their functional behavior. Thus, there is a strong demand for the development of new parameters which can only be determined via the measurement of area. With special respect to the application of deterministically textured topographies in metal forming, appropriate 3d surface parameters can be derived from the mechanical rheological model recently developed at the Institute of Manufacturing Technology. These are the maximum ratio of closed void area and the closed void volume, both of which result from a special evaluation of the bearing ratio curves. Industrial applications show that these parameters can be related to the functionality of the surface and hence may be regarded as very suitable for the characterization and qualification of complex surface structures.
LFT Import::2019-07-16 (1989)
Keywords: Forming; Rolling; Topography